PERANAN GOOD CORPORATE GOVERNANCE TERHADAP KUALITAS PELAPORAN KEUANGAN DAN KEPERCAYAAN INVESTOR - THERESIA ADELIA SIMADIBRATA (Universitas Katolik Widya Mandala Surabaya, 2012)
Financial report has been used by the investors to make a decision making during investment. The best quality of financial report related with Good Corporate Governance of a company. A company must adopt and apply the principles of Good Corporate Governance. By doing these principles, the company expected to have good internal management, so they could make a better quality of financial report.Good Corporate Governance is required to control the behavior of corporate managers act in order not to benefit himself, his own so as to give investors confidence to invest. Good Corporate Governance principles are transparency, accountability, fairness and responsibility. The existence of good corporate governance, it is expected that an increase in the company's internal performance management through performance monitoring and management accountability to other stakeholders.